2020
DOI: 10.1093/heapol/czaa151
|View full text |Cite
|
Sign up to set email alerts
|

Health equity funds as the pathway to universal coverage in Cambodia: care seeking and financial risk protection

Abstract: Cambodia has developed the health equity fund (HEF) system to improve access to health services for the poor, and this strengthens the health system towards the universal health coverage goal. Given rising healthcare costs, Cambodia has introduced several innovations and accomplished considerable progress in improving access to health services and catastrophic health expenditures for the targeted population groups. Though this is improving in recent years, HEF households remain at the higher risk of catastroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Previous studies revealed that HEF membership contributed to the health service uptake at public facilities and reduced healthcare expenditure in general users. 16 27 Our findings extended the understanding that HEF membership has also increased public healthcare use and substantially reduced healthcare spending among people with T2D and/or HTN. Since HEF benefits are only available in public healthcare facilities, it is not surprising that it also contributes to increasing service uptake in public facilities.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies revealed that HEF membership contributed to the health service uptake at public facilities and reduced healthcare expenditure in general users. 16 27 Our findings extended the understanding that HEF membership has also increased public healthcare use and substantially reduced healthcare spending among people with T2D and/or HTN. Since HEF benefits are only available in public healthcare facilities, it is not surprising that it also contributes to increasing service uptake in public facilities.…”
Section: Discussionsupporting
confidence: 70%
“…In the project we studied, the choice was to introduce and implement a HIF, which is a variant of health equity funds (HEFs), where third-party organizations (often NGOs) are responsible for identifying the poorest and financing their access to care. These approaches have been well-documented in Cambodia and the experience has been reported in several publications (9,16,17). It is interesting to note, however, that HEFs have not "gone mainstream."…”
Section: Discussionmentioning
confidence: 94%
“…There is mixed evidence as to if the HEF increases public health service utilization due to issues with gaps in financial risk protection, general low utilization of public providers, and deficient eligibility targeting [ 10 ]. However, a direct comparison of utilization rates by service level and type demonstrates that public health service utilization among HEF beneficiaries is generally higher compared to the rest of the population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, systematic factors can lead to patient avoidance of public facilities due to quality perceptions including competency and attitude of providers [ 78 ]. Another factor is limited service availability, particularly for non-communicable diseases [ 10 ]. Moreover, it is also possible that patients may avoid public care-seeking due to unofficial fees or face substantial indirect financial shocks relating to needed medical care and/or lost productivity [ 20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation